The exceptional child inclusion in early childhood education - Allen, K. Eileen 1918-; Cowdery, Glynnis Edwards (Cengage Learning, 2015)
Filled with research about all aspects of educating young children with special needs, this book discusses key approaches and tools needed to provide an optimal setting for young exceptional children with special needs and their families.